On some verb final suffixes in Mongolian and Manchu Languages - E, Munkhtsetseg (Altaica, 2024)
The bilingual Manchu-Mongolian dictionary compiled during the reign of the emperor Kangxi (published in 1717) is an explanatory dictionary organized in subject order. Each verb as well as all other words in the dictionary is supplied by a commentary which explains its meaning. The paper deals with the Manchu and Mongolian verb determining Suffixes. Their commentaries explain the meanings sometimes different from the generally known ones. Монгол, манж хэлний үйл үгийн зарим төгсгөх нөхцөлийн тухайд манж, монгол хэлний үйлийн төгсгөх нөхцөл, тэдгээрийн утгыг Чингийн үеийн толь бичгийн дурсгалуудаас тодруулах боломжтой юм. Энэхүү өгүүлэлд 1717 онд найруулан бичсэн «Хааны бичсэн манж, монгол үгний толь бичиг»-ийг судлагдахуун болгон авч, түүнд агуулагдаж буй мэдээлэлд түшиглэн монгол, манж хэлний цагаар төгсгөх нөхцөлийн онцлог шинжийг илрүүлэхийг оролдлоо. Түлхүүр үг: толь бичиг, толгой үг, тайлбар, үйл үг, үйлийн төгсгөх нөхцөл, утга